Herramienta para mejorar la afinación vocal en Android - Menchén Martín, Ramón; Barbancho-Pérez, Ana María; Herrero-Platero, María Inés; Tardón-García, Lorenzo José; Barbancho-Pérez, Isabel (Juan Córcoles Ortega, Julián Fiérrez Aguilar, José M. Martínez Sánchez, José L. Masa Campos, Javier Ortega García, Jorge A. Ruiz Cruz, 2016)
In this paper, a tool to improve vocal tuning in Android devices is presented. This application aims to offer exercises to practice and improve singing skills. The designed tool includes two main functionalities: sound synthesis, to provide with singing sound references, and fundamental frequency analysis, to analize the sound and check if the user sings the right musical note. The well-known Yin algorithm has been selected to perform the fundamental frequency analysis. Three different singing exercises are included: sing single notes, sing intervals and sing a note in order to complete a chord. The system also includes a graphical interface in which musical notation is employed to write down the singing sound. The system has been evaluated in order to test out its correct performance regarding both the analysis and synthesis of musical sounds.
Keywords: Canto -- Estudios y ejercicios; Afinación vocal; Herramienta Android; Reconocimiento notas; Deteccion voz cantada